Late gadolinium enhancement‐MRI determines definite lesion formation most accurately at 3 months post ablation compared to later time points. Issue 1 (15th December 2021) - Althoff, Till F.; Garre, Paz; Caixal, Gala; Perea, Rosario; Prat, Susanna; Tolosana, Jose Maria; Guasch, Eduard; Roca‐Luque, Ivo; Arbelo, Elena; Sitges, Marta; Brugada, Josep; Mont, Lluís
Abstract: Aims: Neither the long‐term development of ablation lesions nor the capability of late gadolinium enhancement (LGE)‐MRI to detect ablation‐induced fibrosis at late stages of scar formation have been defined. We sought to assess the development of atrial ablation lesions over time using LGE‐MRI and invasive electroanatomical mapping (EAM). Methods and Results: Ablation lesions and total atrial fibrosis were assessed in serial LGE‐MRI scans 3 months and >12 months post pulmonary vein (PV) isolation. High‐density EAM performed in subsequent repeat ablation procedures served as a reference. Serial LGE‐MRI of 22 patients were analyzed retrospectively. The PV encircling ablation lines displayed an average LGE, indicative of ablation‐induced fibrosis, of 91.7% ± 7.0% of the circumference at 3 months, but only 62.8% ± 25.0% at a median of 28 months post ablation ( p < 0.0001). EAM performed in 18 patients undergoing a subsequent repeat procedure revealed that the consistent decrease in LGE over time was owed to a reduced detectability of ablation‐induced fibrosis by LGE‐MRI at time‐points > 12 months post ablation. Accordingly, the agreement with EAM regarding detection of ablation‐induced fibrosis and functional gaps was good for the LGE‐MRI at 3 months ( κ .74; p < .0001), but only weak for the LGE‐MRI at 28 months post‐ablation ( κ .29; p < .0001). Conclusion: While non‐invasive lesion assessment with LGE‐MRI 3 months post ablation provides accurate guidance for future redo‐procedures, detectability of atrial ablation lesions appears to decrease over time. Thus, it should be considered to perform LGE‐MRI 3 months post‐ablation rather than at later time‐points > 12 months post ablation, like for example, prior to a planned redo‐ablation procedure.